Clinical and laboratory findings in referrals for mitochondrial DNA analysis. Issue 1 (1st July 1998) - Lamont, P J; Surtees, R; Woodward, C E; Leonard, J V; Wood, N W; Harding, A E
Abstract : BACKGROUND: Increasingly, mutations of mitochondrial DNA (mtDNA) are being considered when investigating the aetiology of neurological diseases in childhood. However, they are often difficult to predict clinically. METHOD: Mitochondrial DNA analysis was carried out on 190 children from 1992 to 1996. Most patients were screened for large scale rearrangements and point mutations at nucleotide positions 3243, 3271, 8344, and 8993. RESULTS: Mutations were found in only 15 patients (7.9%) and were either large scale rearrangements (seven patients) or point mutations at nucleotide position 3243 (eight patients). Other point mutations were screened for depending on the clinical picture. The age of symptom onset was significantly older in children with an mtDNA mutation (mean 7.0 years) compared with children without a mutation (mean 2.8 years). Neither Leigh's syndrome (28 cases) nor severe infantile lactic acidosis (12 cases) was associated with mtDNA mutation. Only three clinical features were significantly associated with an mtDNA mutation: progressive external ophthalmoplegia, myopathy, and pigmentary retinopathy. Family history was valuable: the point mutation at nucleotide 3243 (but not the large scale rearrangements) was associated with maternal inheritance; and consanguinity was not associated with mtDNA mutations. The only investigation that provided specific evidence of an underlying mtDNA mutation was histochemical staining of muscle biopsy specimens. The large scale mutations associated with Kearns-Sayre syndrome and progressive external ophthalmoplegia were found in DNA from muscle only, not leucocyte DNA; whereas point mutations were found in leucocyte DNA. CONCLUSIONS: Even among children seen at a neurogenetic referral centre, mtDNA mutations were very uncommon. Muscle biopsy was the only investigation to provide evidence of mtDNA abnormality.